Multiscale Causes of Persistent Heavy Rainfall in the Meiyu Period over the Middle and Lower Reaches of the Yangtze River - Xia, Yicong; Huang, Qian; Yao, Suxiang; Sun, Tianle (Frontiers in Earth Science, 2021)
Based on observation data supplied by the Chinese Meteorological Administration (CMA) and reanalysis datasets provided by the ECMWF, the multiscale causes of persistent heavy rainfall events (PHREs) that occurred from 1979-2018 during Meiyu periods over the middle and lower reaches of the Yangtze River (MLYR) are investigated. During Meiyu periods, precipitation shows obvious interannual variabilities. In PHRE years, the contribution rate of persistent heavy rainfall to the total precipitation is approximately 57%. Precipitation also shows significant synoptic-scale (less than 10 days) characteristics. Through the quantitative diagnosis of interactions among background-scale (greater than 30 days), quasi-biweekly-scale (10-30-day), and synoptic-scale variables, the possible causes of PHREs are explored. The results reveal that the difference in precipitation intensity between PHRE years and non-PHRE years is determined by the background water vapor, background wind and synoptic-scale wind conditions. In PHRE years, the prevailing background southwesterly winds from lower latitudes provide more background water vapor, and more mean kinetic energy is converted to perturbation energy. Moreover, the active synoptic-scale oscillations from higher latitudes and the convergence of Rossby wave disturbance energy over the MLYR could also cause the occurrence and maintenance of PHREs during Meiyu periods.